Positive electrode active material particle, positive electrode and lithium iron battery
Patent Information
- Application Number
- JP2023127491
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-04
- Publication Date
- 2025-02-17
- Estimated Expiration
- 2043-08-04
AI Technical Summary
【0007】 Mgの濃度が表面部よりも内部で高い場合、Liの拡散の抑制や電子伝導性の阻害等の影響が小さくなる結果、初期抵抗の増加が抑制されるものと考えられる。また、Mgを含むことにより、充放電に伴う正極活物質粒子のc軸長の伸長が抑制されるため、内部のクラックの発生が抑制される結果、容量維持率の低下が抑制されるものと考えられる。
Smart Images

Figure 2025023403000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to positive electrode active material particles, positive electrodes, and lithium ion batteries. [Background technology]
[0002] Patent Document 1 (JP 2018-88383 A) discloses a positive electrode active material for a non-aqueous electrolyte secondary battery, which contains magnesium (Mg) and has a concentration gradient such that the Mg concentration decreases in the direction from the particle surface toward the center. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2018-88383 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, if the concentration of Mg is high on the particle surface, the resistance, especially the initial resistance, may increase due to the suppression of lithium (Li) diffusion, the inhibition of electronic conductivity, etc. Furthermore, if Mg is present only on the particle surface, cracks may occur inside due to the difference in the expansion and contraction of the c-axis length between the outside and inside of the positive electrode active material during charging and discharging, and the capacity retention rate may decrease.
[0005] An object of the present disclosure is to suppress an increase in initial resistance and a decrease in capacity retention rate. [Means for solving the problem]
[0006] [1] Positive electrode active material particles, The positive electrode active material particles have a layered rock salt type crystal structure, The positive electrode active material particles contain a lithium composite oxide containing magnesium, The positive electrode active material particles have a higher magnesium concentration inside the positive electrode active material particles than a magnesium concentration in a surface portion of the positive electrode active material particles.
[0007] It is believed that when the Mg concentration is higher in the interior than in the surface, the effects of suppressing Li diffusion, inhibiting electronic conductivity, etc. are reduced, thereby suppressing an increase in initial resistance. In addition, the inclusion of Mg suppresses the elongation of the c-axis length of the positive electrode active material particles accompanying charge and discharge, thereby suppressing the occurrence of internal cracks, and thus suppressing a decrease in the capacity retention rate.
[0008] [2] The concentration of magnesium in the interior is 0.5 mol% or more and 8.0 mol% or less, The positive electrode active material particles according to [1], wherein the magnesium concentration in the surface portion is 5.0 mol % or less.
[0009] [3] The positive electrode active material particles according to [1] or [2], wherein the difference between the magnesium concentration in the interior and the magnesium concentration in the surface portion is 1.0 mol % or more.
[0010] [4] A positive electrode comprising the positive electrode active material particles according to any one of [1] to [3]. [5] The positive electrode according to [4], further comprising carbon nanotubes.
[0011] [6] A lithium ion battery comprising the positive electrode according to [4] or [5]. [Brief description of the drawings]
[0012] [Figure 1] FIG. 1 is a cross-sectional view of a positive electrode active material particle in this embodiment. [Diagram 2] FIG. 2 is a conceptual diagram showing an example of a lithium ion battery in this embodiment. [Diagram 3] FIG. 3 is a table showing the first battery configuration. [Figure 4] FIG. 4 is a table showing the second battery configuration. [Diagram 5]FIG. 5 is a table showing the third battery configuration. [Figure 6] FIG. 6 is a table showing the sample configurations and evaluation results of the examples and comparative examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the present disclosure (hereinafter may be abbreviated as "the present embodiment") and an example of the present disclosure (hereinafter may be abbreviated as "the present embodiment") will be described. However, the present embodiment and the example do not limit the technical scope of the present disclosure.
[0014] The stoichiometric composition formula shows a representative example of a compound. The compound may have a non-stoichiometric composition. For example, "Al2O3" is not limited to a compound having a substance ratio (molar ratio) of "Al / O=2 / 3". "Al2O3" shows a compound containing Al and O in any composition ratio unless otherwise specified. Furthermore, for example, the compound may be doped with a trace element, or a part of Al and O may be replaced with another element.
[0015] The term "derivative" refers to a compound in which a part of a parent compound has been modified by at least one method selected from the group consisting of introduction of a functional group, substitution of an atom, oxidation, reduction, and other chemical reactions. The modification may be at one or more locations. The "substituent" may include at least one selected from the group consisting of, for example, an alkyl group, an alkenyl group, an alkynyl group, a cycloalkyl group, an unsaturated cycloalkyl group, an aromatic group, a heterocyclic group, a halogen atom (F, Cl, Br, I, etc.), an OH group, an SH group, a CN group, an SCN group, an OCN group, a nitro group, an alkoxy group, an unsaturated alkoxy group, an amino group, an alkylamino group, a dialkylamino group, an aryloxy group, an acyl group, an alkoxycarbonyl group, an acyloxy group, an aryloxycarbonyl group, an acylamino group, an alkoxycarbonylamino group, an aryloxycarbonylamino group, a sulfonylamino group, a sulfamoyl group, a carbamoyl group, an alkylthio group, an arylthio group, a sulfonyl group, a sulfinyl group, a ureido group, a phosphoric acid amide group, a sulfo group, a carboxy group, a hydroxamic acid group, a sulfino group, a hydrazino group, an imino group, and a silyl group. These substituents may be further substituted. When there are two or more substituents, the substituents may be the same or different. A plurality of substituents may be bonded to each other to form a ring.
[0016] The "copolymer" includes at least one type selected from the group consisting of an unspecified type, a statistical type, a random type, an alternating type, a periodic type, a block type, and a graft type.
[0017] <<Cathode active material particles>> 1 is a cross-sectional view of a positive electrode active material particle in this embodiment. The positive electrode active material particle 5 has a layered rock salt type crystal structure. The positive electrode active material particle 5 includes a lithium composite oxide containing Mg. The Mg concentration in the interior 1 of the positive electrode active material particle 5 is higher than the Mg concentration in the surface portion 2 of the positive electrode active material particle 5.
[0018] The positive electrode active material particles 5 have a layered rock salt type crystal structure. The crystal structure of the positive electrode active material 5 can be identified by, for example, inductively coupled plasma atomic emission spectroscopy (ICP-AES) or the like.
[0019] The positive electrode active material particles 5 contain a lithium composite oxide containing Mg. The composition of the lithium composite oxide containing Mg is not limited as long as the positive electrode active material particles 5 have a layered rock salt type crystal structure.
[0020] The Mg concentration (mol%) in the inside 1 of the positive electrode active material particle 5 is higher than the Mg concentration (mol%) in the surface portion 2 of the positive electrode active material particle 5. That is, the positive electrode active material particle 5 has a different composition between the inside 1 and the surface portion 2. By increasing the Mg concentration in the inside 1 of the positive electrode active material particle 5, the influence of the inhibition of Li diffusion and the inhibition of electronic conductivity is reduced, and as a result, it is expected that the increase in initial resistance is suppressed. In addition, the extension of the c-axis length of the positive electrode active material particle 5 accompanying charge and discharge is suppressed, and therefore the occurrence of cracks in the inside 1 is suppressed, and as a result, it is expected that the decrease in the capacity retention rate is suppressed. The Mg concentration in the inside 1 of the positive electrode active material particle 5 may be higher than that of the surface portion 2 of the positive electrode active material particle 5, and for example, the Mg concentration in the surface portion 2 of the positive electrode active material particle 5 may be 0 mol%. In addition, the Mg concentration in the positive electrode active material particle 5 may be continuously increased, for example, from the surface portion 2 of the positive electrode active material particle 5 toward the inside 1.
[0021] In this embodiment, the "interior of the positive electrode active material particle" refers to the center of gravity of the positive electrode active material particle and the region in the vicinity thereof, and typically refers to the region 100 nm or more inward from the outermost surface of the positive electrode active material particle toward the center of gravity. For example, when the positive electrode active material particle is a substantially spherical particle, the region within 100 nm from the center of gravity of the smallest circle circumscribing the particle can be regarded as the interior of the positive electrode active material particle. In addition, the "surface portion of the positive electrode active material particle" refers to the area from the surface of the positive electrode active material particle to a depth of 50 nm.
[0022] The composition of the lithium composite oxide containing Mg is, for example, in the inner part 1, represented by the following formula (1).
[0023] Li a Ni (1-b) Mg b O c (1) In the above formula (1), a satisfies the relationship of 1.00≦a≦1.20, b satisfies the relationship of 0.005≦b≦0.08, and c satisfies the relationship of 2.0≦c<2.1. b is preferably 0.01≦b≦0.06, and may be 0.02≦b≦0.05.
[0024] The composition of the Mg-containing lithium composite oxide in the surface portion 2 is represented by the following formula (2), for example.
[0025] Li x Ni (1-y) Mg y O z (2) In the above formula (2), x satisfies the relationship of 1.00≦x≦1.20, y satisfies the relationship of 0.00≦y≦0.05, and z satisfies the relationship of 2.0≦z<2.1. For example, y may be 0.001≦y≦0.05 or 0.002≦y≦0.04.
[0026] The Mg concentration in the inside 1 and the surface portion 2 of the positive electrode active material particle 5 in this embodiment can be confirmed by, for example, using a transmission electron microscope (TEM)-energy dispersive X-ray spectroscopy (EDX). Specifically, first, as a measurement object, any positive electrode active material particle 5 is embedded in an appropriate resin, and cross-section polishing or the like is performed to expose the cross section of the positive electrode active material particle 5. Next, this cross section is observed with a TEM at an appropriate magnification. In the obtained TEM observation image, the center of gravity and the outermost surface of the positive electrode active material particle 5 are analyzed by EDX to obtain the respective Mg atom concentrations (mol%). In addition, it is preferable to perform a line analysis by EDX on a straight line from any point located on the outermost surface of the positive electrode active material particle 5 to the center of gravity. The line analysis allows the transition of the Mg atom concentration from the surface to the center of gravity of the positive electrode active material particle 5 to be accurately grasped.
[0027] The Mg concentration in the interior 1 of the positive electrode active material particle 5 may be 0.5 mol% or more and 8.0 mol% or less, preferably 1.0 mol% or more and 6.0 mol% or less, or 2.0 mol% or more and 5.0 mol% or less. The Mg concentration in the surface portion 2 of the positive electrode active material particle 5 may be 5.0 mol% or less, preferably 0.1 mol% or more and 5.0 mol% or less, or 0.2 mol% or more and 4.0 mol% or less.
[0028] The difference between the Mg concentration in the interior 1 of the positive electrode active material particle 5 and the Mg concentration in the surface portion 2 of the positive electrode active material particle 5 is preferably 1.0 mol% or more. When the difference satisfies the above range, it is possible to further suppress the increase in the initial resistance and the decrease in the capacity maintenance rate. The difference between the Mg concentration in the interior 1 of the positive electrode active material particle 5 and the Mg concentration in the surface portion 2 of the positive electrode active material particle 5 may more preferably be 2.0 mol% or more, 2.5 mol% or more, or 3.0 mol% or more. However, from the viewpoint of the production of the positive electrode active material particle 5, it may be, for example, 5.0 mol% or less.
[0029] The crystallite diameter of the positive electrode active material particle 5 may be 450 Å or more and 900 Å or less. Here, the crystallite refers to a region (gathering) that can be regarded as a single crystal in the crystal structure in one particle constituting the positive electrode active material particle 5, and the crystallite diameter refers to the size of the crystallite. The crystallite diameter can be calculated based on the Scherrer formula based on the X-ray diffraction (XRD) line profile. In addition, the crystallite diameter of the positive electrode active material particle 5 in this embodiment can be calculated based on the (003) plane that appears as a main peak in the X-ray diffraction line profile. For example, the crystallite diameter of the positive electrode active material particle 5 can be obtained by calculating the half-width of the (003) plane observed in the range of 2θ=19.1 to 20.1 in the spectrum obtained by XRD measurement using the Scherrer formula.
[0030] The positive electrode active material particles 5 are typically secondary particles formed by aggregation of primary particles. The positive electrode active material particles 5 may have an average particle size (D50) of, for example, 4.0 μm or more and 8.0 μm or less, or may have a D50 of 5.0 μm or more and 7.0 μm or less. Here, D50 indicates a particle size at which the cumulative frequency from the small particle size side reaches 50% in a volume-based particle size distribution. D50 can be measured by a laser diffraction method.
[0031] The shape of the positive electrode active material particles 5 is not particularly limited, but examples thereof include a substantially spherical shape, a flake shape, a columnar shape, and the like, and a substantially spherical shape is preferable. Note that the term "substantially spherical" also includes a sphere, a rugby ball shape, a polygonal shape, and the like, and refers to a shape having an average aspect ratio (the ratio of the length in the long axis direction to the length in the shortest rectangle circumscribing the particle) of 1 to 2, for example.
[0032] The positive electrode active material particles 5 may contain, for example, a transition metal oxide, a polyanion compound, or the like.
[0033] <Transition metal oxides: space group R-3m> The transition metal oxide may have any crystal structure. The transition metal oxide may include, for example, a crystal structure belonging to the space group R-3m. For example, a compound represented by the general formula "LiMO2" may have a crystal structure belonging to the space group R-3m. The transition metal oxide may be represented, for example, by the following formula (A-1).
[0034] Li 1-a Ni x M 1-x O2…(A-1) In the formula, the relationship -0.5 ≦ a ≦ 0.5 and 0 ≦ x ≦ 1 is satisfied.
[0035] M may include at least one selected from the group consisting of Co, Mn, and Al.
[0036] In the above formula (A-1), x may satisfy, for example, the relationship 0 < x ≦ 0.1, 0.1 ≦ x ≦ 0.2, 0.2 ≦ x ≦ 0.3, 0.3 ≦ x ≦ 0.4, 0.4 ≦ x ≦ 0.5, 0.5 ≦ x ≦ 0.6, 0.6 ≦ x ≦ 0.7, 0.7 ≦ x ≦ 0.8, 0.8 ≦ x ≦ 0.9, or 0.9 ≦ x ≦ 1. a may satisfy, for example, the relationship -0.4 ≦ a ≦ 0.4, -0.3 ≦ a ≦ 0.3, -0.2 ≦ a ≦ 0.2, or -0.1 ≦ a ≦ 0.1.
[0037] The transition metal oxide may include, for example, at least one selected from the group consisting of LiCoO2, LiMnO2, LiNi 0.9 Co 0.1 O2, LiNi 0.9 Mn 0.1 O2, and LiNiO2.
[0038] 〈NCM〉 The transition metal oxide may be represented, for example, by the following formula (A-2). The compound represented by the following formula (A-2) may also be referred to as "NCM".
[0039] Li 1-a Ni x Co y Mn z O2…(A-2) In the formula, the relationships of -0.5 ≦ a ≦ 0.5, 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1 are satisfied.
[0040] In the above formula (A-2), x may satisfy, for example, the relationship of 0 < x ≦ 0.1, 0.1 ≦ x ≦ 0.2, 0.2 ≦ x ≦ 0.3, 0.3 ≦ x ≦ 0.4, 0.4 ≦ x ≦ 0.5, 0.5 ≦ x ≦ 0.6, 0.6 ≦ x ≦ 0.7, 0.7 ≦ x ≦ 0.8, 0.8 ≦ x ≦ 0.9, or 0.9 ≦ x < 1.
[0041] In the above formula (A-2), y may satisfy, for example, the relationship of 0 < y ≦ 0.1, 0.1 ≦ y ≦ 0.2, 0.2 ≦ y ≦ 0.3, 0.3 ≦ y ≦ 0.4, 0.4 ≦ y ≦ 0.5, 0.5 ≦ y ≦ 0.6, 0.6 ≦ y ≦ 0.7, 0.7 ≦ y ≦ 0.8, 0.8 ≦ y ≦ 0.9, or 0.9 ≦ y < 1.
[0042] In the above formula (A-2), z may satisfy, for example, the relationship of 0 < z ≦ 0.1, 0.1 ≦ z ≦ 0.2, 0.2 ≦ z ≦ 0.3, 0.3 ≦ z ≦ 0.4, 0.4 ≦ z ≦ 0.5, 0.5 ≦ z ≦ 0.6, 0.6 ≦ z ≦ 0.7, 0.7 ≦ z ≦ 0.8, 0.8 ≦ z ≦ 0.9, or 0.9 ≦ z < 1.
[0043] NCM is, for example, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.4 Co 0.3 Mn 0.3 O2, LiNi 0.3 Co 0.4 Mn 0.3 O2, LiNi 0.3 Co 0.3 Mn 0.4 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.5 Co 0.3 Mn 0.2 O2, LiNi 0.5 Co 0.4 Mn 0.1 O2, LiNi 0.5 Co 0.1 Mn0.4 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.6 Co 0.3 Mn 0.1 O2, LiNi 0.6 Co 0.1 Mn 0.3 O2, LiNi 0.7 Co 0.1 Mn 0.2 O2, LiNi 0.7 Co 0.2 Mn 0.1 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2 and LiNi 0.9 Co 0.05 Mn 0.05 It may contain at least one selected from the group consisting of O2.
[0044] 〈NCA〉 The transition metal oxide may be represented, for example, by the following formula (A-3). The compound represented by the following formula (A-3) may also be referred to as "NCA".
[0045] Li 1-a Ni x Co y Al z O2…(A-3) In the formula, the relationships of -0.5 ≦ a ≦ 0.5, 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1 are satisfied.
[0046] In the above formula (A-3), x may satisfy, for example, the relationship of 0 < x ≦ 0.1, 0.1 ≦ x ≦ 0.2, 0.2 ≦ x ≦ 0.3, 0.3 ≦ x ≦ 0.4, 0.4 ≦ x ≦ 0.5, 0.5 ≦ x ≦ 0.6, 0.6 ≦ x ≦ 0.7, 0.7 ≦ x ≦ 0.8, 0.8 ≦ x ≦ 0.9, or 0.9 ≦ x < 1.
[0047] In the above formula (A-3), y may satisfy a relationship such as 0 < y ≤ 0.1, 0.1 ≤ y ≤ 0.2, 0.2 ≤ y ≤ 0.3, 0.3 ≤ y ≤ 0.4, 0.4 ≤ y ≤ 0.5, 0.5 ≤ y ≤ 0.6, 0.6 ≤ y ≤ 0.7, 0.7 ≤ y ≤ 0.8, 0.8 ≤ y ≤ 0.9, or 0.9 ≤ y < 1.
[0048] In the above formula (A-3), z may satisfy a relationship such as 0 < z ≤ 0.1, 0.1 ≤ z ≤ 0.2, 0.2 ≤ z ≤ 0.3, 0.3 ≤ z ≤ 0.4, 0.4 ≤ z ≤ 0.5, 0.5 ≤ z ≤ 0.6, 0.6 ≤ z ≤ 0.7, 0.7 ≤ z ≤ 0.8, 0.8 ≤ z ≤ 0.9, or 0.9 ≤ z < 1.
[0049] NCA is, for example, LiNi 0.7 Co 0.1 Al 0.2 O2, LiNi 0.7 Co 0.2 Al 0.1 O2, LiNi 0.8 Co 0.1 Al 0.1 O2, LiNi 0.8 Co 0.17 Al 0.03 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, and, LiNi 0.9 Co 0.05 Al 0.05 It may contain at least one selected from the group consisting of O2.
[0050] 〈Multi-component system〉 The positive electrode active material particles 5 may contain, for example, two or more types of NCM or the like. The positive electrode active material particles 5 may contain, for example, NCM(0.6 ≤ x) and NCM(x < 0.6). "NCM(0.6 ≤ x)" refers to a compound in which x (Ni ratio) is 0.6 or more in the above formula (A-2). NCM(0.6 ≤ x) may be referred to as, for example, "high nickel material". NCM(0.6 ≤ x) is, for example, LiNi 0.8 Co 0.1 Mn 0.1O2, etc. "NCM (x<0.6)" refers to a compound in which x (Ni ratio) is less than 0.6 in the above formula (A-2). NCM (x<0.6) is, for example, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, etc. The mixing ratio (mass ratio) of NCM(0.6≦x) and NCM(x<0.6) may be, for example, "NCM(0.6≦x) / NCM(x<0.6)=9 / 1 to 1 / 9," "NCM(0.6≦x) / NCM(x<0.6)=9 / 1 to 4 / 6," or "NCM(0.6≦x) / NCM(x<0.6)=9 / 1 to 3 / 7."
[0051] The positive electrode active material particles 5 may contain, for example, NCA and NCM. The mixing ratio (mass ratio) of NCA and NCM may be, for example, "NCA / NCM=9 / 1 to 1 / 9", "NCA / NCM=9 / 1 to 4 / 6", or "NCA / NCM=9 / 1 to 3 / 7". The Ni ratios of NCA and NCM may be the same or different. The Ni ratio of NCA may be higher than the Ni ratio of NCM. The Ni ratio of NCA may be lower than the Ni ratio of NCM.
[0052] <Transition metal oxides: space group C2 / m> The transition metal oxide may have, for example, a crystal structure belonging to the space group C2 / m. The transition metal oxide may be represented by, for example, the following formula (A-4).
[0053] Li2MO3…(A-4) In the formula, M may include, for example, at least one selected from the group consisting of Ni, Co, Mn, and Fe.
[0054] The positive electrode active material particles 5 may include, for example, a mixture of LiMO2 (space group R-3m) and Li2MO3 (space group C2 / m). The positive electrode active material particles 5 may include, for example, a solid solution of LiMO2 and Li2MO3 (Li2MO3-LiMO2).
[0055] <Transition metal oxides: space group Fd-3m> The transition metal oxide may include, for example, a crystal structure belonging to the space group Fd-3m. The transition metal oxide may be represented by, for example, the following formula (A-5).
[0056] LiMn 2-x M x O4…(A-5) In the formula, the relationship 0≦x≦2 is satisfied.
[0057] M may include, for example, at least one selected from the group consisting of Ni, Fe, and Zn.
[0058] LiM2O4 (space group Fd-3m) is, for example, LiMn2O4 and LiMn 1.5 Ni 0.5 The positive electrode active material particles 5 may contain at least one selected from the group consisting of LiMO2 (space group R-3m) and LiM2O4 (space group Fd-3m). The mixture ratio (mass ratio) of LiMO2 (space group R-3m) and LiM2O4 (space group Fd-3m) may be, for example, "LiMO2 / LiM2O4=9 / 1 to 9 / 1", "LiMO2 / LiM2O4=9 / 1 to 5 / 5", or "LiMO2 / LiM2O4=9 / 1 to 7 / 3".
[0059] <Polyanion Compound> The polyanion compound may include, for example, a phosphate (for example, LiFePO4, etc.), a silicate, a borate, etc. The polyanion compound may be represented, for example, by the following formulas (A-6) to (A-9).
[0060] LiMPO4…(A-6) Li 2-x MPO4F...(A-7) Li2MSiO4…(A-8) LiMBO3…(A-9) In the above formulas (A-6) to (A-9), M may, for example, include at least one selected from the group consisting of Fe, Mn, and Co. In the above formula (A-7), for example, the relationship 0≦x≦2 may be satisfied.
[0061] The positive electrode active material particles 5 may contain, for example, a mixture of LiMO2 (space group R-3m) and a polyanion compound. The mixture ratio (mass ratio) of LiMO2 (space group R-3m) and the polyanion compound may be, for example, "LiMO2 / polyanion compound=9 / 1 to 9 / 1", "LiMO2 / polyanion compound=9 / 1 to 5 / 5", or "LiMO2 / polyanion compound=9 / 1 to 7 / 3".
[0062] Dopant A dopant may be added to the positive electrode active material particles 5. The dopant may be diffused throughout the particles or distributed locally. For example, the dopant may be unevenly distributed on the particle surface. The dopant may be a substitutional solid solution atom or an interstitial solid solution atom. The amount of dopant added (molar fraction relative to the entire positive electrode active material particles 5) may be, for example, 0.01 to 5%, 0.1 to 3%, or 0.1 to 1%. One type of dopant may be added, or two or more types of dopants may be added. Two or more types of dopants may form a complex.
[0063] The dopant may include at least one selected from the group consisting of, for example, B, C, N, halogens, Si, Na, Mg, Al, Mn, Co, Cr, Sc, Ti, V, Cu, Zn, Ga, Ge, Se, Sr, Y, Zr, Nb, Mo, In, Pb, Bi, Sb, Sn, W, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, and actinides.
[0064] For example, the set "Zr, Mg, W, Sm", the set "Ti, Mn, Nb, Si, Mo", or the set "Er, Mg" may be added to the NCA.
[0065] For example, Ti may be added to the NCM. For example, a combination of "Zr, W", a combination of "Si, W", or a combination of "Zr, W, Al, Ti, Co" may be added to the NCM.
[0066] Surface coating The positive electrode may include a composite particle. The composite particle includes a core particle and a coating layer. The core particle includes a positive electrode active material particle 5. The coating layer covers at least a part of the surface of the core particle. The coating layer may have a thickness of, for example, 1 to 3000 nm, 5 to 2000 nm, 10 to 1000 nm, 10 to 100 nm, or 10 to 50 nm. The thickness of the coating layer can be measured, for example, in a SEM (Scanning Electron Microscope) image of the particle cross section. That is, the composite particle is embedded in a resin material to prepare a sample. The sample is subjected to a cross-section processing by an ion milling device. For example, an ion milling device "Product name ArBlade (registered trademark) 5000" (or an equivalent product) manufactured by Hitachi High-Technologies Corporation may be used. The cross section of the sample is observed by SEM. For example, an SEM device "Product name SU8030" (or an equivalent product) manufactured by Hitachi High-Technologies Corporation may be used. The thickness of the coating layer is measured in 20 fields for each of 10 composite particles, and the arithmetic mean of the thicknesses of 200 points in total is taken.
[0067] The proportion of the surface of the core particle that is covered by the coating layer is also referred to as the "coverage." The coverage may be, for example, 1% or more, 10% or more, 30% or more, 50% or more, or 70% or more. The coverage may be, for example, 100% or less, 90% or less, or 80% or less.
[0068] The coverage can be measured, for example, by XPS (X-ray Photoelectron Spectroscopy). For example, an XPS device manufactured by ULVAC-PHI, Inc., product name: PHI X-tool (or equivalent) may be used. A sample powder consisting of composite particles is set in the XPS. Narrow scan analysis is performed. The measurement data is processed by analysis software. For example, analysis software manufactured by ULVAC-PHI, Inc., product name: MulTiPak (or equivalent) may be used. The measurement data is analyzed to detect multiple elements. The ratio of each detected element is calculated from the area of each peak. The coverage is calculated by the following formula.
[0069] θ={I1 / (I0+I1)}×100 θ: Coverage rate [%] I0: Ratio of elements originating from the core particle I1: Ratio of elements originating from the coating layer For example, if the core particle contains NCM, I0 indicates the total element ratio of "Ni, Co, Mn". For example, if the core particle contains NCA, I0 indicates the total element ratio of "Ni, Co, Al". For example, if the coating layer contains P and B, I1 indicates the total element ratio of "P, B".
[0070] The coating layer may contain any component. The coating layer may contain, for example, an element, an organic substance, an inorganic acid salt, an organic acid salt, a hydroxide, an oxide, a carbide, a nitride, a sulfide, a halide, or the like. The coating layer may contain, for example, B, Al, W, Zr, Ti, Co, F, a lithium compound (e.g., Li2CO3, LiHCO3, LiOH, Li2O, etc.), tungsten oxide (e.g., WO3, etc.), titanium oxide (e.g., TiO2, etc.), zirconium oxide (e.g., ZrO2, etc.), boron oxide, boron phosphate (e.g., BPO4, etc.), aluminum oxide (e.g., Al2O3, etc.), boehmite, aluminum hydroxide, phosphate (e.g., Li3PO 4、(NH4)3PO4, AlPO4, etc.), borates (e.g., Li2B4O7, LiBO3, etc.), polyacrylates (Li salts, Na salts, NH4 salts, etc.), acetates (e.g., Li salts, etc.), CMC (acid type, Na salts, Li salts, NH4 salts, etc.), LiNbO 3、 It may contain at least one selected from the group consisting of Li2TiO3 and Li-containing halides (for example, LiAlCl4, LiTiAlF6, LiYBr6, LiYCl6, etc.).
[0071] <Hollow particles / Solid particles> "Hollow particles" refer to secondary particles in which the area ratio of the cavity in the center in a cross-sectional image is 30% or more of the cross-sectional area of the entire particle. The ratio of the cavity in a hollow particle may be, for example, 40% or more, 50% or more, or 60% or more. "Solid particles" refer to secondary particles in which the area ratio of the cavity in the center in a cross-sectional image of the particle is less than 30% of the cross-sectional area of the entire particle. The ratio of the cavity in a solid particle may be, for example, 20% or less, 10% or less, or 5% or less. The positive electrode active material particles 5 may be hollow particles or solid particles. A mixture of hollow particles and solid particles may be used. The mixing ratio (mass ratio) of hollow particles to solid particles may be, for example, "hollow particles / solid particles=1 / 9 to 9 / 1," "hollow particles / solid particles=2 / 8 to 8 / 2," "hollow particles / solid particles=3 / 7 to 7 / 3," or "hollow particles / solid particles=4 / 6 to 6 / 4."
[0072] <Large particles / Small particles> "Electrode active material" is a general term for positive electrode active material and negative electrode active material. The electrode active material may have, for example, a unimodal particle size distribution (based on number). The electrode active material may have, for example, a multimodal particle size distribution. The electrode active material may have, for example, a bimodal particle size distribution. That is, the electrode active material may contain large particles and small particles. When the particle size distribution is bimodal, the particle size corresponding to the peak top of the larger particle size is the particle size of the large particles (d L The particle size corresponding to the peak top with the smaller particle size is considered to be the particle size of the small particles (d S ) is considered as the particle size ratio (dL / d S ) may be, for example, 2 to 10, 2 to 5, or 2 to 4. L may be, for example, 8 to 20 μm, or 8 to 15 μm. S may be, for example, 1 to 10 μm, or 1 to 5 μm.
[0073] For example, the particle size distribution may be subjected to peak separation processing using waveform analysis software. L ) and the peak area due to small particles (S S ) is expressed as, for example, "S L / S S =1 / 9~9 / 1", "S L / S S =5 / 5~9 / 1" or "S L / S S =7 / 3~9 / 1".
[0074] The particle size distribution based on the number is measured by a microscopy method. A plurality of cross-sectional samples are taken from the electrode active material layer. The cross-sectional samples may include, for example, a cross section perpendicular to the surface of the electrode active material layer. For example, the surface to be observed is cleaned by ion milling or the like. The cross-sectional samples are observed by SEM. The observation magnification is adjusted so that 10 to 100 particles are contained within the observation field of view. The Feret diameters of all particles in the image are measured. The "Feret diameter" refers to the distance between the two most distant points on the contour line of a secondary particle. By observing a plurality of cross-sectional samples, a total of 1000 or more Feret diameters are obtained. A particle size distribution based on the number is created from the 1000 or more Feret diameters.
[0075] A bimodal particle size distribution can be formed by mixing two kinds of particles. The two kinds of particles have different particle size distributions. For example, the two kinds of particles may have different D50s. "D50" indicates a particle size at which the cumulative frequency from the small particle size side reaches 50% in a volume-based particle size distribution. D50 can be measured by a laser diffraction method. The measurement sample is a powder. For example, the large particles may have a D50 of 8 to 20 μm, or 8 to 15 μm. For example, the small particles may have a D50 of 1 to 10 μm, or 1 to 5 μm. The ratio of the D50 of the large particles to the D50 of the small particles may be, for example, 2 to 10, 2 to 5, or 2 to 4. The mixing ratio (mass ratio) of the large particles to the small particles may be, for example, "large particles / small particles=1 / 9 to 9 / 1," "large particles / small particles=5 / 5 to 9 / 1," or "large particles / small particles=7 / 3 to 9 / 1."
[0076] The large particles and the small particles may have the same composition or different compositions. For example, the large particles may be NCA and the small particles may be NCM. For example, the large particles may be NCM (0.6≦x) and the small particles may be NCM (x<0.6).
[0077] <<Method of manufacturing positive electrode active material particles>> The positive electrode active material particles in this embodiment can be produced, for example, by the following method, however, the following description is merely an example and is not intended to limit the production method.
[0078] The method for producing the positive electrode active material particles in this embodiment includes, for example, "(A) Preparation of a precursor" and "(B) Calcination".
[0079] (A) Preparation of precursor The manufacturing method includes preparing a precursor of the positive electrode active material particles. The precursor may be prepared by any method. For example, a mixed hydroxide of Mg and a transition metal (for example, Ni) is prepared. The mixed hydroxide powder is, for example, ground in a mortar. For example, the ground mixed hydroxide powder is dissolved in an alkaline aqueous solution to form a mixed solution. The alkaline aqueous solution may contain, for example, an NaOH aqueous solution and an ammonia solution. For example, an acidic aqueous solution and an alkaline aqueous solution are simultaneously dropped into the mixed solution to form a precipitate. During the dropping, the pH can be adjusted. The precipitate is considered to contain a composite hydroxide (precursor). The precipitate is washed and dried to form a dry product.
[0080] Alternatively, sulfates of Mg and a transition metal (e.g., Ni) are prepared. The sulfates are dissolved in water to form an acidic aqueous solution. For example, an alkaline aqueous solution may be added dropwise to the acidic aqueous solution to cause a neutralization reaction. The alkaline aqueous solution may contain, for example, an aqueous NaOH solution and aqueous ammonia. A precipitate may be formed by the neutralization reaction. In the neutralization reaction, the pH may be adjusted. The precipitate is thought to contain a precursor. The precipitate is washed and dried to form a dry product.
[0081] <(B) Firing> The resulting dried material is mixed with a lithium compound to form a mixture. The lithium compound may include, for example, Li2CO3, LiOH, etc. The mixture is subjected to a heat treatment (firing). The firing temperature may be, for example, 500 to 1000°C. The firing time may be, for example, 5 to 30 hours. In this manner, positive electrode active material particles are produced.
[0082] <<Lithium-ion batteries>> 2 is a conceptual diagram showing an example of a lithium ion battery in this embodiment. The battery 100 includes a power generating element 50 and an electrolyte (not shown).
[0083] <Exterior body> The battery 100 may include an exterior body (not shown). The exterior body may house the power generating element 50 and the electrolyte. The exterior body may have any shape. The exterior body may be, for example, a metal case or a pouch made of a metal foil laminated film. The case may have any shape. The case may be, for example, cylindrical, rectangular, flat, coin-shaped, or the like. The exterior body may include, for example, Al, or the like. The exterior body may house, for example, one power generating element 50, or may house a plurality of power generating elements 50. The plurality of power generating elements 50 may form, for example, a series circuit or a parallel circuit. In the exterior body, the plurality of power generating elements 50 may be stacked in the thickness direction of the battery 100.
[0084] <Power generation elements> The power generating element 50 may also be referred to as an "electrode group", an "electrode body", or the like. The power generating element 50 includes a positive electrode 10 and a negative electrode 20. The power generating element 50 may further include a separator 30. The separator 30 is disposed between the positive electrode 10 and the negative electrode 20. The power generating element 50 may have any shape. The power generating element 50 may be, for example, a laminated type. For example, the power generating element 50 may be formed by alternately laminating the positive electrode 10 and the negative electrode 20 while sandwiching the separator 30 between the positive electrode 10 and the negative electrode 20. The power generating element 50 may be, for example, a wound type. For example, a strip-shaped positive electrode 10, a strip-shaped separator 30, and a strip-shaped negative electrode 20 may be laminated to form a laminate. The laminate may be spirally wound to form the power generating element 50. The wound type power generating element 50 may be formed into a flat shape after winding.
[0085] <Positive electrode> The positive electrode 10 may be, for example, in the form of a sheet. The positive electrode 10 includes a positive electrode collector 11 and a positive electrode active material layer 12. The positive electrode collector 11 has electrical conductivity. The positive electrode collector 11 supports the positive electrode active material layer 12. The positive electrode collector 11 may be, for example, in the form of a sheet. The positive electrode collector 11 may have a thickness of, for example, 5 to 50 μm. The positive electrode collector 11 may include, for example, a metal foil. The positive electrode collector 11 may include, for example, at least one selected from the group consisting of Al, Mn, Ti, Fe, and Cr. The positive electrode collector 11 may include, for example, an Al foil, an Al alloy foil, a Ti foil, a stainless steel (SUS) foil, or the like.
[0086] An intermediate layer (not shown) may be formed between the positive electrode current collector 11 and the positive electrode active material layer 12. The intermediate layer does not contain positive electrode active material particles. The intermediate layer may have a thickness of, for example, 0.1 to 5 μm. The intermediate layer may contain, for example, a conductive material, an insulating material, a binder, etc. The conductive material and the binder will be described later. The insulating material may contain, for example, alumina, boehmite, aluminum hydroxide, etc.
[0087] The positive electrode active material layer 12 is disposed on the surface of the positive electrode collector 11. The positive electrode active material layer 12 may be disposed on only one side of the positive electrode collector 11. The positive electrode active material layer 12 may be disposed on both the front and back sides of the positive electrode collector 11. The positive electrode active material layer 12 may have a thickness of, for example, 10 μm or more, 50 μm or more, 80 μm or more, or 100 μm or more. When the thickness of the positive electrode active material layer 12 is large, specifically, when the thickness is 80 μm or more, it is considered that the durability maintenance rate is further improved. In addition, the positive electrode active material layer 12 may have a thickness of 1000 μm or less, 500 μm or less, or 300 μm or less. The positive electrode active material layer 12 includes positive electrode active material particles. The positive electrode active material layer 12 may further include, for example, a conductive material, a binder, carbon nanotubes, and the like.
[0088] Conductive materials The conductive material can form an electronic conduction path in the positive electrode active material layer 12. The amount of the conductive material may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the positive electrode active material particles. The conductive material can contain any component. The conductive material may contain, for example, at least one selected from the group consisting of graphite, acetylene black (AB), Ketjen Black (registered trademark), vapor grown carbon fiber (VGCF), carbon nanotube (CNT), and graphene flake (GF).
[0089] Binder The binder can fix the positive electrode active material layer 12 to the positive electrode current collector 11. The amount of the binder may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the positive electrode active material particles. The binder may contain any component. The binder may contain, for example, at least one selected from the group consisting of polyvinylidene fluoride (PVdF), vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), tetrafluoroethylene (PTFE), CMC, PAA, polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), polyoxyethylene alkyl ether, and derivatives thereof.
[0090] Carbon nanotubes Carbon nanotubes (CNTs) have high electronic conductivity. Therefore, by including CNTs in the positive electrode active material layer 12, electronic conductivity is ensured, and as a result, improvements in initial resistance and capacity retention rate are expected. In addition, it is preferable that the CNTs are contained inside the positive electrode active material particles. It is believed that by including the CNTs inside the positive electrode active material particles, the CNTs are compounded and electronic conductivity is further ensured.
[0091] The CNT may have, for example, an aspect ratio of 20 or more. When the CNT has an aspect ratio of 20 or more, the CNT is easily contained in the interior 1 of the positive electrode active material particle 5, and a reduction in resistance is expected. The CNT may have an aspect ratio of 100 or more.
[0092] The aspect ratio is the ratio of length to diameter. In this specification, the "aspect ratio" is determined by dividing the average length of the CNTs by the average diameter of the CNTs. The average length and average diameter can each be the arithmetic mean of measurements of 10 or more CNTs. The length and diameter of each CNT are measured by TEM or Scanning Electron Microscope (SEM).
[0093] The CNTs may have, for example, an average diameter of 10 nm to 50 nm, and an average length of 1 μm to 5 μm.
[0094] The CNT content in the positive electrode active material layer 12 may be, for example, 0.1% by mass or more and 5.0% by mass or less. When the CNT content in the positive electrode active material layer 12 satisfies the above range, improvements in the initial resistance and capacity retention rate are expected. The CNT content in the positive electrode active material layer 12 is preferably 0.5% by mass or more and 4.0% by mass or less.
[0095] Other Ingredients The positive electrode active material layer 12 may further contain, for example, an inorganic filler, an organic filler, a solid electrolyte, a surface modifier, a lubricant, a flame retardant, a protective agent, a flux, a coupling agent, an adsorbent, etc. The positive electrode active material layer 12 may further contain, for example, polyoxyethylene allyl phenyl ether phosphate, zeolite, a silane coupling agent, MoS2, WO3, etc.
[0096] <Negative electrode> The negative electrode 20 may be, for example, in a sheet shape. The negative electrode 20 may include, for example, a negative electrode collector 21 and a negative electrode active material layer 22. The negative electrode collector 21 has electrical conductivity. The negative electrode collector 21 supports the negative electrode active material layer 22. The negative electrode collector 21 may be, for example, in a sheet shape. The negative electrode collector 21 may have a thickness of, for example, 5 to 50 μm. The negative electrode collector 21 may include, for example, a metal foil or the like. The negative electrode collector 21 may include, for example, at least one selected from the group consisting of Cu, Ni, Fe, Zn, Pb, Ag, and Au. The negative electrode collector 21 may include, for example, a Cu foil, a Cu alloy foil, or the like.
[0097] The negative electrode active material layer 22 is disposed on the surface of the negative electrode current collector 21. The negative electrode active material layer 22 may be disposed on only one surface of the negative electrode current collector 21. The negative electrode active material layer 22 may be disposed on both the front and back surfaces of the negative electrode current collector 21. The negative electrode active material layer 22 may have a thickness of, for example, 10 to 1000 μm, 50 to 500 μm, or 100 to 300 μm. The negative electrode active material layer 22 contains a negative electrode active material. The negative electrode active material layer may further contain, for example, a conductive material and a binder.
[0098] The negative electrode active material layer 22 may have a thickness of, for example, 10 to 1000 μm, 50 to 500 μm, or 100 to 300 μm. The negative electrode active material layer 22 contains a negative electrode active material. The negative electrode active material layer may further contain, for example, a conductive material and a binder.
[0099] Conductive materials The conductive material can form an electron conduction path in the negative electrode active material layer 22. The content of the conductive material may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the negative electrode active material. The conductive material may contain any component. The conductive material may contain, for example, at least one selected from the group consisting of graphite, AB, Ketjen Black, VGCF, CNT, and GF. The CNT may contain at least one selected from the group consisting of single-walled CNT (SWCNT) and multi-walled CNT (MWCNT).
[0100] Binder The binder can fix the negative electrode active material layer 22 to the negative electrode current collector 21. The content of the binder may be, for example, 0.1 to 10 parts by mass with respect to 100 parts by mass of the negative electrode active material. The binder may contain any component. The binder may contain, for example, at least one selected from the group consisting of styrene butadiene rubber (SBR), acrylate butadiene rubber (ABR), sodium alginate, carboxymethyl cellulose (CMC-H, CMC-Na, CMC-Li, CMC-NH4, etc.), polyacrylic acid (PAA-H, PAA-Na, PAA-Li, etc.), polyacrylonitrile (PAN), polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), acrylic resin (acrylic acid ester copolymer), methacrylic resin (methacrylic acid ester copolymer), polyvinylpyrrolidone (PVP), polyvinyl alcohol (PVA), and derivatives thereof. For example, "CMC-Na" refers to the Na salt of CMC. For example, "CMC-H" refers to the acid form of CMC. The same applies to "PAA-Na" and the like.
[0101] Other Ingredients The negative electrode active material layer 22 may further contain, for example, an inorganic filler, an organic filler, a solid electrolyte, a surface modifier, a dispersant, a lubricant, a flame retardant, a protective agent, a flux, a coupling agent, an adsorbent, etc. The negative electrode active material layer may further contain, for example, a layered silicate (smectite, montmorillonite, bentonite, hectorite, etc.), an inorganic filler (solid alumina, hollow silica, boehmite, etc.), a polysiloxane compound, etc.
[0102] 《Negative electrode active material》 Examples of the negative electrode active material include natural graphite, artificial graphite, soft carbon, hard carbon, silicon (Si), SiO, Li silicate, Si-based alloy, tin (Sn), SnO, Sn-based alloy, and Li4Ti5O 12 may contain at least one selected from the group consisting of:
[0103] Carbon-based active material "Graphite" is a general term for natural graphite and artificial graphite. Graphite may be a mixture of natural graphite and artificial graphite. The mixing ratio (mass ratio) may be, for example, "natural graphite / artificial graphite = 1 / 9 to 9 / 1", "natural graphite / artificial graphite = 2 / 8 to 8 / 2", or "natural graphite / artificial graphite = 3 / 7 to 7 / 3".
[0104] Graphite may contain a dopant. The dopant may contain, for example, at least one selected from the group consisting of B, N, P, Li, and Ca. The addition amount may be, for example, 0.01 to 5%, 0.1 to 3%, or 0.1 to 1% in molar fraction.
[0105] The surface of the graphite may be coated with, for example, amorphous carbon. The surface of the graphite may be coated with, for example, a different material. The different material may contain, for example, at least one selected from the group consisting of P, W, Al, and O. The different material may contain, for example, at least one selected from the group consisting of Al(OH)3, AlOOH, Al2O3, WO3, Li2CO3, LiHCO 3、 and at least one selected from the group consisting of Li3PO4.
[0106] 〈Alloy-based active material〉 SiO may be represented, for example, by the following formula (B-1).
[0107] SiO x …(B-1) In the formula, the relationship of 0 < x < 2 is satisfied.
[0108] In the above formula (B-1), x may satisfy, for example, 0.5 ≤ x ≤ 1.5, or 0.8 ≤ x ≤ 1.2.
[0109] The Li silicate may include at least one selected from the group consisting of Li4SiO4, Li2SiO3, Li2Si2O5, and Li8SiO6. The second negative electrode active material may include a mixture of Si and Li silicate. The mixture ratio (mass ratio) may be, for example, "Si / Li silicate = 1 / 9 to 9 / 1", "Si / Li silicate = 2 / 8 to 8 / 2", "Si / Li silicate = 3 / 7 to 7 / 3", or "Si / Li silicate = 4 / 6 to 6 / 4".
[0110] The alloy-based active material (Si, SiO, etc.) may contain an additive. The additive may be, for example, a substitutional solid solution atom or an interstitial solid solution atom. The additive may be an attachment attached to the surface of the alloy-based active material. The attachment may be, for example, an element, an oxide, a carbide, a nitride, a halide, etc. The amount of addition may be, for example, 0.01 to 5%, 0.1 to 3%, or 0.1 to 1% in molar fraction. The additive may contain, for example, at least one selected from the group consisting of Li, Na, K, Rb, Be, Mg, Ca, Sr, Fe, Ba, B, Al, Ga, In, C, Ge, Sn, Pb, N, P, As, Y, Sb, and S. That is, SiO may be doped with Mg or Na. For example, Mg silicate or Na silicate may be formed. For example, boron oxide (eg, B2O3), yttrium oxide (eg, Y2O3, etc.), etc. may be added to SiO.
[0111] <Si-C composite material> The negative electrode active material may include, for example, a composite material of a carbon-based active material (such as graphite) and an alloy-based active material (such as Si). A composite material containing Si and carbon may also be called a "Si-C composite material". For example, Si fine particles may be dispersed in carbon particles. For example, Si fine particles may be dispersed in graphite particles. For example, Li silicate particles may be coated with a carbon material (such as amorphous carbon). The Si-C composite material and graphite may be mixed and used.
[0112] <Multi-component system> The negative electrode active material may contain two or more components. The negative electrode active material may contain a carbon-based active material (such as graphite) and an alloy-based active material (such as Si, SiO). The mixing ratio (mass ratio) of the carbon-based active material and the alloy-based active material may be, for example, "carbon-based active material / alloy-based active material=1 / 9 to 9 / 1", "carbon-based active material / alloy-based active material=2 / 8 to 8 / 2", "carbon-based active material / alloy-based active material=3 / 7 to 7 / 3", or "carbon-based active material / alloy-based active material=4 / 6 to 6 / 4".
[0113] <separator> The separator 30 can separate the positive electrode 10 from the negative electrode 20. The separator 30 has electrical insulation properties. The separator 30 may include at least one selected from the group consisting of a resin film, an inorganic particle layer, and an organic particle layer. The separator 30 may include, for example, a resin film and an inorganic particle layer.
[0114] Resin film The resin film is porous. The resin film may include, for example, a microporous film, a nonwoven fabric, etc. The resin film includes a resin skeleton. The resin skeleton may be continuous, for example, in a network form. Pores are formed in the gaps of the resin skeleton. The resin film can allow an electrolyte to pass through. The resin film may have an average pore size of, for example, 1 μm or less. The resin film may have an average pore size of, for example, 0.01 to 1 μm, or 0.1 to 0.5 μm. The "average pore size" can be measured by mercury intrusion porosimetry. The resin film may have a pore size of, for example, 50 to 250 s / 100 cm. 3 The "Gurley value" may be measured by the Gurley test method.
[0115] The resin film may contain at least one selected from the group consisting of, for example, olefin-based resins, polyurethane-based resins, polyamide-based resins, cellulose-based resins, polyether-based resins, acrylic-based resins, and polyester-based resins. The resin film may contain at least one selected from the group consisting of, for example, polyethylene (PE), polypropylene (PP), polyamide (PA), polyamideimide (PAI), polyimide (PI), aromatic polyamide (aramid), polyphenylene ether (PPE), and derivatives thereof. The resin film may be formed by, for example, a stretching method, a phase separation method, or the like. The resin film may have a thickness of, for example, 5 to 50 μm, or 10 to 25 μm.
[0116] The resin film may have, for example, a single-layer structure. The resin film may be composed of, for example, a PE layer. The skeleton of the PE layer is formed of PE. The PE layer may have a shutdown function. The resin film may have, for example, a multi-layer structure. The resin film may include, for example, a PP layer and a PE layer. The skeleton of the PP layer is formed of PP. The resin film may have, for example, a three-layer structure. The resin film may be formed by laminating, for example, a PP layer, a PE layer, and a PP layer in this order. The thickness of the PE layer may be, for example, 5 to 20 μm. The thickness of the PP layer may be, for example, 3 to 10 μm.
[0117] 《Inorganic particle layer》 The inorganic particle layer may be formed on the surface of the resin film. The inorganic particle layer may be formed on only one side of the resin film, or on both sides. The inorganic particle layer may be formed on the surface facing the positive electrode 10, or on the surface facing the negative electrode 20. The inorganic particle layer may be formed on the surface of the positive electrode 10, or on the surface of the negative electrode 20.
[0118] The inorganic particle layer is porous. The inorganic particle layer includes inorganic particles. The inorganic particles may also be called "inorganic filler". Pores are formed in the gaps between the inorganic particles. The inorganic particle layer may have a thickness of, for example, 0.5 to 10 μm, or 1 to 5 μm. The inorganic particles may include, for example, a heat-resistant material. The inorganic particle layer including a heat-resistant material is also called "HRL (Heat Resistance Layer)". The inorganic particles may include at least one selected from the group consisting of boehmite, alumina, zirconia, titania, magnesia, silica, and the like. The inorganic particles may have any shape. The inorganic particles may be, for example, spherical, rod-like, plate-like, fibrous, and the like. The inorganic particles may have a D50 of, for example, 0.1 to 10 μm, or 0.5 to 3 μm. The inorganic particle layer may further include a binder. The binder may contain at least one selected from the group consisting of, for example, acrylic resins, polyamide resins, fluorine resins, aromatic polyether resins, and liquid crystal polyester resins.
[0119] 《Organic particle layer》 The separator 30 may include, for example, an organic particle layer. The separator 30 may include, for example, an organic particle layer instead of a resin film. The separator 30 may include, for example, an organic particle layer instead of an inorganic particle layer. The separator 30 may include both a resin film and an organic particle layer. The separator 30 may include both an inorganic particle layer and an organic particle layer. The separator 30 may include a resin film, an inorganic particle layer, and an organic particle layer.
[0120] The organic particle layer may have a thickness of, for example, 0.1 to 50 μm, 0.5 to 20 μm, 0.5 to 10 μm, or 1 to 5 μm. The organic particle layer includes organic particles. The organic particles may also be referred to as "organic filler". The organic particles may include a heat-resistant material. The organic particles may include at least one selected from the group consisting of, for example, PE, PP, PTFE, PI, PAI, PA, and aramid. The organic particles may be, for example, spherical, rod-like, plate-like, fibrous, or the like. The organic particles may have a D50 of, for example, 0.1 to 10 μm, or 0.5 to 3 μm.
[0121] Separator 30 may, for example, include a mixed layer that includes both inorganic and organic particles.
[0122] <Electrolyte> The electrolyte has Li ions dissolved therein. The electrolyte may be a liquid electrolyte or a gel electrolyte. The liquid electrolyte may include, for example, an electrolytic solution. The electrolytic solution includes a solvent and a solute.
[0123] "solvent" <Ether Solvent> The electrolytic solution may contain, for example, an ether-based solvent. The solvent may contain, for example, hydrofluoroether (HFE). The HFE may contain at least one selected from the group consisting of, for example, a difluoromethyl group, a 2,2-difluoroethyl group, a 2,2,2-trifluoroethyl group, a 1,1,2,2-tetrafluoroethyl group, a 2,2,3,3,3-pentafluoropropyl group, a 2,2,3,3-tetrafluoropropyl group, a 1,1,1,3,3,3-hexafluoroisopropyl group, a 1,1,2,3,3,3-hexafluoropropyl group, a 2,2,3,3,4,4,4-heptafluorobutyl group, a 2,2,3,3,4,4-hexafluorobutyl group, and a 2,2,3,3,4,4,5,5-octafluoropentyl group.
[0124] The solvent may also contain an ether other than HFE (hereinafter also referred to as "second ether"). The second ether may contain, for example, at least one selected from the group consisting of tetrahydrofuran (THF), 1,4-dioxane (DOX), 1,3-dioxolane (DOL), 1,2-dimethoxyethane (DME), 1,2-diethoxyethane (DEE), ethylglyme, triglyme, tetraglyme, and derivatives thereof. The solvent may contain, for example, 1 to 50% by volume of the second ether (DME, etc.), and the balance being HFE. The solvent may contain, for example, 10 to 40% by volume of the second ether, and the balance being HFE.
[0125] <Carbonate-based solvent> The electrolytic solution may contain, for example, a carbonate-based solvent (carbonate ester-based solvent). The solvent may contain, for example, a cyclic carbonate, a chain carbonate, a fluorinated carbonate, or the like. The solvent may contain, for example, at least one selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), monofluoroethylene carbonate (FEC), difluoroethylene carbonate, 4,4-difluoroethylene carbonate, trifluoroethylene carbonate, perfluoroethylene carbonate, fluoropropylene carbonate, difluoropropylene carbonate, and derivatives thereof.
[0126] The solvent may contain a cyclic carbonate (EC, PC, FEC, etc.) and a chain carbonate (EMC, DMC, DEC, etc.). The mixing ratio (volume ratio) of the cyclic carbonate to the chain carbonate may be, for example, "cyclic carbonate / chain carbonate=1 / 9 to 4 / 6", "cyclic carbonate / chain carbonate=2 / 8 to 3 / 7", or "cyclic carbonate / chain carbonate=3 / 7 to 4 / 6".
[0127] The solvent may contain a cyclic carbonate (EC, PC, etc.) and a fluorinated cyclic carbonate (FEC, etc.). The mixing ratio (volume ratio) of the cyclic carbonate and the fluorinated cyclic carbonate may be, for example, "cyclic carbonate / fluorinated cyclic carbonate=99 / 1 to 90 / 10", "cyclic carbonate / fluorinated cyclic carbonate=9 / 1 to 1 / 9", "cyclic carbonate / fluorinated cyclic carbonate=9 / 1 to 7 / 3", or "cyclic carbonate / fluorinated cyclic carbonate=3 / 7 to 1 / 9".
[0128] The solvent may contain, for example, EC, FEC, EMC, DMC, and DEC. The volume ratio of each component may satisfy, for example, the relationship represented by the following formula (C-1).
[0129] V EC +V FEC +V EMC +V DMC +V DEC =10 ...(C-1) In the formula, V EC , V FEC , V EMC , V DMC , V DEC indicates the volume ratio of EC, FEC, EMC, DMC, and DEC, respectively.
[0130] 1≦V EC ≦4, 0≦V FEC ≦3,V EC +V FEC ≦4, 0≦V EMC ≦9, 0≦V DMC ≦9, 0≦V DEC ≦9, 6≦V EMC +V DMC +V DEC ≦9 The relationship is satisfied.
[0131] In the above formula (C-1), For example, 1≦V EC ≦2, or 2≦V EC The relationship ≦3 may be satisfied.
[0132] For example, 1≦V FEC ≦2, or 2≦V FEC The relationship ≦4 may be satisfied. For example, 3≦V EMC ≦4 or 6≦V EMC The relationship ≦8 may be satisfied.
[0133] For example, 3≦V DMC ≦4 or 6≦V DMC The relationship ≦8 may be satisfied. For example, 3≦V DEC ≦4 or 6≦V DEC The relationship ≦8 may be satisfied.
[0134] The solvent may have a composition, for example, by volume, of "EC / EMC=3 / 7", "EC / DMC=3 / 7", "EC / FEC / DEC=1 / 2 / 7", "EC / DMC / EMC=3 / 4 / 3", "EC / DMC / EMC=3 / 3 / 4", "EC / FEC / DMC / EMC=2 / 1 / 4 / 3", "EC / FEC / DMC / EMC=1 / 2 / 4 / 3", "EC / FEC / DMC / EMC=2 / 1 / 3 / 4", "EC / FEC / DMC / EMC=1 / 2 / 3 / 4", or the like.
[0135] Additives The electrolyte may contain any additive. The amount of additive (mass fraction relative to the total electrolyte) may be, for example, 0.01 to 5%, 0.05 to 3%, or 0.1 to 1%. The additive may include, for example, an SEI (Solid Electrolyte Interphase) formation promoter, an SEI formation inhibitor, a gas generating agent, an overcharge inhibitor, a flame retardant, an antioxidant, an electrode protector, a surfactant, and the like.
[0136] Examples of the additives include vinylene carbonate (VC), vinyl ethylene carbonate (VEC), 1,3-propane sultone (PS), tert-amylbenzene, 1,4-di-tert-butylbenzene, biphenyl (BP), cyclohexylbenzene (CHB), ethylene sulfite (ES), propane sultone (PS), ethylene sulfate (DTD), γ-butyrolactone, phosphazene compounds, carboxylic acid esters (e.g., methyl formate (MF), methyl acetate (MA), methyl propionate (MP), diethyl malonate (DEM), etc.), fluorobenzenes (e.g., monofluorobenzene (FB), 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, 1,3,5-trifluorobenzene, 1,2,3,4-tetrafluorobenzene, 1,2,3,5-tetrafluorobenzene, 1,2,4,5-tetrafluorobenzene, pentafluorobenzene, hexafluorobenzene, etc.), fluorotoluenes (e.g., 2-fluorotoluene, 3-fluorotoluene, 4-fluorotoluene, 2,3-difluorotoluene, 2,4-difluorotoluene, 2,5-difluorotoluene, 2,6-difluorotoluene, 3,4-difluorotoluene, octafluorotoluene, etc.), benzotrifluorides (e.g., benzotrifluoride, 2-fluorobenzotrifluoride, 3-fluorobenzotrifluoride, 4-fluorobenzotrifluoride, 2-methylbenzotrifluoride, 3-methylbenzotrifluoride, 4-methylbenzotrifluoride, etc.), fluoroxylenes (e.g., 3-fluoro-o-xylene, 4-fluoro-o-xylene, 2-fluoro-m-xylene, 5-fluoro-m-xylene, etc.), sulfur-containing heterocyclic compounds (e.g., benzothiazole, 2-methylbenzyl The solvent may contain at least one selected from the group consisting of anhydrides (e.g., benzothiazole, tetrathiafulvane, etc.), nitrile compounds (e.g., adiponitrile, succinonitrile, etc.), phosphates (e.g., trimethyl phosphate, triethyl phosphate, etc.), carboxylic acid anhydrides (e.g., acetic anhydride, propionic anhydride, oxalic anhydride, succinic anhydride, maleic anhydride, phthalic anhydride, benzoic anhydride, etc.), alcohols (e.g., methanol, ethanol, n-propyl alcohol, ethylene glycol, diethylene glycol monomethyl ether, etc.), and derivatives thereof.
[0137] The components described above as solutes and solvents may be used as minor components (additives). The additives may include at least one selected from the group consisting of LiBF4, LiFSI, LiTFSI, LiBOB, LiDFOB, LiDFOP, LiPO2F2, FSO3Li, LiI, LiBr, HFE, DOX, PC, FEC, and derivatives thereof.
[0138] <Ionic Liquid> The liquid electrolyte may include an ionic liquid. The liquid electrolyte may include at least one selected from the group consisting of a sulfonium salt, an ammonium salt, a pyridinium salt, a piperidinium salt, a pyrrolidinium salt, a morpholinium salt, a phosphonium salt, an imidazolium salt, and derivatives thereof.
[0139] Gel electrolyte The gel electrolyte may include a liquid electrolyte and a polymer material. The polymer material may form a polymer matrix. The polymer material may include at least one selected from the group consisting of PVdF, PVdF-HFP, PAN, PVdF-PAN, polyethylene oxide (PEO), polyethylene glycol (PEG), and derivatives thereof.
[0140] <Battery configuration> FIG. 3 is a table showing the first battery configuration. FIG. 4 is a table showing the second battery configuration. FIG. 5 is a table showing the third battery configuration. In each table, when multiple types of materials are described in a box, the description includes each material alone and combinations thereof. For example, when materials "α, β, γ" are described in a box, the description indicates "at least one selected from the group consisting of α, β, and γ." Any element may be extracted from the first to third battery configurations and arbitrarily combined.
[0141] This embodiment may be incorporated into, for example, the first to third battery configurations. The positive electrode in the first battery configuration may be replaced with the positive electrode (positive electrode current collector 11, positive electrode active material layer 12) in this embodiment. The combination of the first to third battery configurations with this embodiment may improve battery performance. EXAMPLES
[0142] The present embodiment will be described below using examples, but the present embodiment is not limited thereto. In the following, the method for producing the positive electrode active material particles in Nos. 2 to 4 may be referred to as the "doping method", the method for producing the positive electrode active material particles in Nos. 5 to 7 as the "MHP method", and the method for producing the positive electrode active material particles in Nos. 8 to 10 as the "post-addition method".
[0143] <Production of Positive Electrode Active Material Particles> (No.1) A nickel sulfate aqueous solution (1.8 mol / L) (hereinafter, mol / L is also simply referred to as "M") was prepared. A precipitate was formed by dropping an NaOH aqueous solution (1.0 M) into the nickel sulfate aqueous solution. The NaOH aqueous solution was dropped while adjusting so as to maintain the pH at 11.6. The precipitate was washed and dried to form a dried product. A mixture was formed by mixing the dried product with LiOH. The mixture was mixed so that the mixture ratio of Li and Ni (Li / Ni) (molar ratio) was 1.04. The mixture was fired. The firing temperature was 880°C. The firing time was 6 hours. As a result, the positive electrode active material particles No. 1 having a layered rock salt structure were synthesized. It is to be noted that the positive electrode active material particles No. 2 to No. 10 described later were also confirmed to have a layered rock salt structure.
[0144] (No.2) Nickel sulfate and magnesium sulfate were dissolved in water to prepare an acidic aqueous solution (1.8M). The mixing ratio (molar ratio) of the solutes was nickel sulfate:magnesium sulfate=96.8:3.2. A NaOH aqueous solution (1.0M) was dropped into the acidic aqueous solution to form a precipitate. The NaOH aqueous solution was dropped while adjusting the pH to maintain 11.6. The precipitate was washed and dried to form a dried product. The dried product was mixed with LiOH to form a mixture. The mixture was mixed so that the mixing ratio (Li / (Ni+Mg)) (molar ratio) of Li to Ni and Mg was 1.04. The firing temperature was 880° C. The firing time was 6 hours. As described above, the positive electrode active material particles of No. 2 were synthesized.
[0145] (No.3~4) Positive electrode active material particles Nos. 3 and 4 were synthesized under the same conditions as No. 2, except that the compounding ratio of the solutes in the acidic aqueous solution in No. 3 was changed to nickel sulfate:magnesium sulfate = 94.4:5.6, and the compounding ratio of the solutes in the acidic aqueous solution in No. 4 was changed to nickel sulfate:magnesium sulfate = 98.7:1.3.
[0146] (No.5) A mixed hydroxide of nickel hydroxide and magnesium hydroxide was prepared. The mixing ratio (molar ratio) was nickel hydroxide:magnesium hydroxide=96.7:3.1. The mixed hydroxide powder was pulverized in a mortar until D50 was approximately 3 μm. The pulverized mixed hydroxide powder was dissolved in ammonia water (mass concentration: 10%) to prepare a mixed solution. A nickel sulfate aqueous solution (1.8 M) and a NaOH aqueous solution (1.0 M) were simultaneously dropped into the mixed solution to form a precipitate. The nickel sulfate aqueous solution and the NaOH aqueous solution were dropped while adjusting the pH to maintain 11.6. The precipitate was washed and dried to form a dried product. The dried product was mixed with LiOH to form a mixture. The mixture was mixed so that the mixing ratio (Li / (Ni+Mg)) (molar ratio) of Li to Ni and Mg was 1.04. The firing temperature was 880° C. The firing time was 6 hours. In this manner, positive electrode active material particles No. 5 were synthesized.
[0147] (No.6~7) Positive electrode active material particles Nos. 6 and 7 were synthesized under the same conditions as No. 5, except that the mixed hydroxide ratio in No. 6 was nickel hydroxide:magnesium hydroxide = 94.2:5.8, and the mixed hydroxide solute ratio in No. 7 was nickel hydroxide:magnesium hydroxide = 99.1:0.9.
[0148] (No.8) Positive electrode active material particles No. 1 were prepared. The positive electrode active material particles and magnesium oxide were mixed to form a mixture. The mixture was mixed so that the mixing ratio of Ni and Mg (Ni:Mg) (molar ratio) was 96.9:3.1. The mixture was fired. The firing temperature was 500° C. The firing time was 5 hours. As a result, positive electrode active material particles No. 8 were synthesized.
[0149] (No.9~10) Positive electrode active material particles Nos. 9 and 10 were synthesized under the same conditions as No. 8, except that the mixing ratio of Ni and Mg in No. 9 was 94.6:5.4, and the mixing ratio of Ni and Mg in No. 10 was 98.9:1.1.
[0150] <Lithium-ion battery manufacturing> Example 1 The positive electrode of Example 1 was prepared using the following materials:
[0151] 《Positive electrode》 Positive electrode active material particles: No.2 Conductive material: AB (Denka Co., Ltd.) Binder: PVDF (Kureha Corporation) Additionally, test batteries for evaluation of Example 1 were fabricated using the following materials:
[0152] 《Negative electrode》 Negative electrode active material: Natural graphite (Hitachi Chemical Co., Ltd.) Binder: CMC (Nippon Paper Industries Co., Ltd.), SBR (JSR Corporation) "others" Separator: Porous sheet (thickness: 24 μm) Electrolyte: Electrolyte [LiPF6(1M), EC+DMC+EMC] Example 2 A positive electrode of Example 2 and a test battery for evaluation were produced under the same conditions as in Example 1, except that the positive electrode active material particles in Example 2 were No. 3.
[0153] (Examples 3 to 5) The positive electrodes and evaluation test batteries of Examples 3 to 5 were produced under the same conditions as Example 1, except that 0.4 mass % of CNT was added to the positive electrode of Example 1, 1.0 mass % of CNT was added to the positive electrode of Example 1, and 4.0 mass % of CNT was added to the positive electrode of Example 1.
[0154] (Examples 6 to 8) The positive electrodes and evaluation test batteries of Examples 6 to 8 were produced under the same conditions as Example 1, except that the positive electrode active material particles in Example 6 were No. 5, the positive electrode active material particles in Example 7 were No. 6, and the positive electrode active material particles in Example 8 were No. 7.
[0155] (Examples 9 to 11) The positive electrodes and evaluation test batteries of Examples 9 to 11 were produced under the same conditions as Example 1, except that 0.4 mass% of CNT was added to the positive electrode of Example 6, 1.0 mass% of CNT was added to the positive electrode of Example 6, and 4.0 mass% of CNT was added to the positive electrode of Example 6.
[0156] Comparative Example 1 A positive electrode of Comparative Example 1 and a test battery for evaluation were produced under the same conditions as in Example 1, except that the positive electrode active material particles in Comparative Example 1 were No. 1.
[0157] Comparative Example 2 A positive electrode of Comparative Example 2 and a test battery for evaluation were produced under the same conditions as in Example 1, except that the positive electrode active material particles in Comparative Example 2 were No. 4.
[0158] (Comparative Examples 3 to 5) Positive electrodes and evaluation test batteries of Comparative Examples 3 to 5 were produced under the same conditions as in Example 1, except that the positive electrode active material particles in Comparative Example 3 were No. 8, the positive electrode active material particles in Comparative Example 4 were No. 9, and the positive electrode active material particles in Comparative Example 5 were No. 10.
[0159] (Comparative Examples 6 to 8) The positive electrodes and evaluation test batteries of Comparative Examples 6 to 8 were produced under the same conditions as Example 1, except that 0.4 mass % of CNT was added to the positive electrode of Comparative Example 3, 1.0 mass % of CNT was added to the positive electrode of Comparative Example 3, and 4.0 mass % of CNT was added to the positive electrode of Comparative Example 3.
[0160] <Analysis> "composition" The compositions of the interior and surface of the positive electrode active material particles No. 1 to 10 were confirmed by ICP-AES. The composition of the interior of the positive electrode active material particle was determined from the composition at the center of gravity of the positive electrode active material particle, and the composition of the surface of the positive electrode active material particle was determined from the composition of the outermost surface of the positive electrode active material particle. The composition of each positive electrode active material particle is shown in FIG. 6.
[0161] Magnesium concentration The Mg concentrations (mol %) in the interior and surface of the positive electrode active material particles Nos. 1 to 10 were confirmed by the above-mentioned TEM-EDX. The Mg concentration in the interior of the positive electrode active material particle was determined as the Mg concentration at the center of gravity of the positive electrode active material particle, and the Mg concentration in the surface portion of the positive electrode active material particle was determined as the Mg concentration in the outermost surface portion of the positive electrode active material particle. The Mg concentrations in the interior and surface portions of each positive electrode active material particle are shown in FIG. 6. In FIG. 6, the difference between the Mg concentration in the interior of the positive electrode active material particle and the Mg concentration in the surface portion of the positive electrode active material particle (interior concentration - surface concentration) is referred to as the "Mg concentration difference."
[0162] <Evaluation> (initial resistance) After charging each test battery to 3.6V, it was discharged at a current value of 10C for 10 seconds in a room temperature environment, and the voltage 10 seconds after the start of discharge was measured. From the result, the IV resistance (electrical resistance) was calculated to obtain the initial resistance. The results are shown in Figure 6. The results are shown as relative values when the initial resistance of the test battery of Comparative Example 1 was set to 100. An initial resistance of 150 or less was considered good.
[0163] (Capacity maintenance rate) After the measurement of the initial resistance, charging and discharging were repeated 100 times at room temperature with a constant current of 1C in the voltage range of 3.0 to 4.2V. After the first charging and discharging, the discharge capacity when charging and discharging with a current of 0.1C in the voltage range of 3.0 to 4.2V was taken as the first discharge capacity, and after the 100th charging and discharging, the discharge capacity when charging and discharging with a current of 0.1C in the voltage range of 3.0 to 4.2V was taken as the 100th discharge capacity. The capacity retention rate (percentage) was calculated by dividing the 200th discharge capacity by the first discharge capacity. The results are shown in FIG. 6. A capacity retention rate of 75% or more was considered to be good.
[0164] <Result> (initial resistance) As shown in FIG. 6, in the examples in which the Mg concentration in the interior of the positive electrode active material particles was higher than the Mg concentration in the surface portions of the positive electrode active material particles, the initial resistance values were good.
[0165] Furthermore, when comparing Example 1 including positive electrode active material particles No. 2 produced by the doping method, Example 6 including positive electrode active material particles No. 5 produced by the MHP method, and Comparative Example 3 including positive electrode active material particles No. 8 produced by the post-addition method, Example 6 produced by the MHP method had the lowest initial resistance, and Comparative Example 3 produced by the post-addition method had the highest initial resistance.
[0166] (Capacity maintenance rate) As shown in FIG. 6, in the examples in which the Mg concentration inside the positive electrode active material particles was higher than the Mg concentration on the surface of the positive electrode active material particles, the capacity retention rate was good even after repeated charge and discharge.
[0167] Furthermore, when comparing Example 1 including positive electrode active material particles No. 2 produced by the doping method, Example 6 including positive electrode active material particles No. 5 produced by the MHP method, and Comparative Example 3 including positive electrode active material particles No. 8 produced by the post-addition method, Example 6 produced by the MHP method had the highest capacity retention rate, and Comparative Example 3 produced by the post-addition method had the lowest capacity retention rate.
[0168] Furthermore, with regard to Examples 9 to 11, which contained the positive electrode active material particles No. 5 produced by the MHP method and CNTs, it was confirmed that the capacity retention rate improved as the CNT content increased, compared to Example 6, which did not contain CNTs.
[0169] It was also confirmed that Examples 6 to 11, which include positive electrode active material particles produced by the MHP method, had a larger difference between the internal Mg concentration and the surface Mg concentration in the positive electrode active material particles compared to Examples 1 to 5, which include positive electrode active material particles produced by the doping method.
[0170] The embodiments and examples disclosed herein should be considered to be illustrative and not restrictive in all respects. The scope of the present disclosure is defined by the claims, not the above description, and is intended to include all modifications within the scope and meaning equivalent to the claims. [Explanation of symbols]
[0171] 1 interior, 2 surface portion, 5 positive electrode active material, 10 positive electrode, 11 positive electrode current collector, 12 positive electrode active material layer, 20 negative electrode, 21 negative electrode current collector, 22 negative electrode active material layer, 30 separator, 50 power generating element, 100 lithium ion battery.
Claims
1. Positive electrode active material particles, The positive electrode active material particles have a layered rock salt type crystal structure, The positive electrode active material particles contain a lithium composite oxide containing magnesium, The positive electrode active material particles have a higher magnesium concentration inside the positive electrode active material particles than a magnesium concentration in a surface portion of the positive electrode active material particles.
2. the concentration of magnesium in the interior is 0.5 mol % or more and 8.0 mol % or less; 2 . The positive electrode active material particle according to claim 1 , wherein the magnesium concentration in the surface portion is 5.0 mol % or less.
3. 2 . The positive electrode active material particle according to claim 1 , wherein a difference between a magnesium concentration in the interior and a magnesium concentration in the surface portion is 1.0 mol % or more.
4. A positive electrode comprising the positive electrode active material particles according to claim 1 .
5. 5. The positive electrode of claim 4 further comprising carbon nanotubes.
6. A lithium ion battery comprising the positive electrode according to claim 4 or 5.
Citation Information
Patent Citations
Lithium-cobalt composite oxide positive electrode material and preparation method and application thereof
CN109585812A
Nonaqueous electrolyte secondary battery
JP2000149950A
Positive electrode material for lithium secondary battery, its manufacturing method and lithium secondary battery
JP2006164859A
Composite electrode active material for lithium battery and method of manufacturing the same
JP2011086603A
Gradient cathode material for lithium secondary batteries
JP4695831B2